Mass Spectrometric Analysis of Histone Proteoforms - Yuan, Zuo-Fei (2014)
Histones play important roles in chromatin, due to various post-translational modifications and sequence variants, which are called histone proteoforms. Investigating modifications and variants is an on-going challenge. Previous methods are based on antibodies and because they usually detect only one modification at a time, they are not suitable to study the various combinations of modifications on histones. Fortunately, mass spectrometry has emerged as a high-throughput technology for histone analysis and does not require prior knowledge about any modifications. From the data generated by mass spectrometers, both identification and quantification of modifications and variants can be easily obtained. Based on this information, the functions of histones in various cellular contexts can be revealed. Therefore, mass spectrometry continues to play an important role in the study of histone proteoforms. In this review, we will discuss the analysis strategies of mass spectrometry, their applications on histones, and some key remaining challenges.